The Using of Bilingual to Write A Visual Identity of Product Labels EFL Economic Students - Umar, Umar; Purwadinata, Subhan (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This study aims to examine the use of bilinguals (local language and English) in writing visual identities on SME product labels for students of the Faculty of Economics. The research problems were; 1) how does the perception of students relates to bilingual teaching materials; and 2) how does the effect of bilingual teaching materials on a visual identity of product labels to enhance students’ English writing? The study was a quantitative descriptive study with pre-test and post-test designs. The data were analyzed using the Statistical Package for Social Sciences (SPSS) 26.0, which was followed by qualitative interpretation. Data from the questionnaire deployed numerical calculation of the percentage, while data from the written test were presented quantitatively. Findings of the study revealed that students’ perceptions of bilingual have very good criteria to improve students’ writing skills (Indicator-A: SA = 40% + A = 50% = 90%; Indicator-B: SA = 40% + A = 50% = 90%, Indicator-C: SA = 60% + A = 40% = 100%, and Indicator-D: SA = 50% + A = 50% = 100%), and have a significant effect on students’ English writing ability (sig. (2-tailed) 0.000 <0.05, and the t-count value of 7.726> t-table 2.09302).